General timetabling system for school - Liew, Sau Poh (Universiti Malaysia Sarawak, UNIMAS, 2005)
The General Timetabling System for School is developed based on the local school timetable structure. The system is implemented using a heuristic generic algorithm that best fit to the timetabling solution. The system is designed on the principle of providing a user-friendly interface for the beginner to learn and use the system with ease. Result of the system testing shown that the system development objectives are successfully achieved. However, there are some limitations on the programming language and database management basis that are still looking for better solution. Additionally, possible future works to improve the usability of the system had also been identified and discussed.